EXPERIMENTAL INFECTION MODEL TO OBTAIN E. GRANULOSUS ADULT FORMS AND SECONDARY HYDATIDIC CYSTIC IN THE GOLDEN HAMSTER (MESOCRICETUS AURATUS) - Vallenas R., Gonzalo (2013)
The objective of the study was to evaluate an alternative animal model to the use of canines as definitive host and the use of sheep as definitive host of Echinococcus granulosus. Thirty three female Golden hamsters (Mesocricetus auratus) were used. In group A, 16 animals of one month of age were orally infected with 3000 viable protoscoleces of E. granulosus; and in group B, 17 animals of 4.5 months of age were intraperitoneal infected with 1500 viable protoscoleces. All protoscoleces were obtained from fertile cysts collected from naturally infected sheep. No adult forms of E. granulosus were recovered from group A, while in group B secondary hydatid cysts were recovered in 9 animals (52.9%) at 2.5, 3.5 and 6.5 months after infection. All recovered cysts were infertile.